Of arcs and circles : Insights from Japan on gardens, nature, and art - Keane, Marc Peter (Stone Bridge Press, 2022)
The essays in this collection delve into the essence of gardens and trees, unearthing the meanings behind their names and unraveling their true composition, explore the mysteries of the torii gates at Shinto shrines, and elucidate the tradition of giving flowers as gifts. Much like the art of a Zen garden, each sentence in this book is thoughtfully placed, offering a contemplative journey that mirrors a leisurely stroll.